Using Multiple Modes of Transcription to Improve the Sentence Typing of Elementary Students With Disabilities. Issue 4 (December 2019) - Datchuk, Shawn M.; Smith, Sydra; Wang, Lanqi
Elementary students are expected to engage in written expression that is handwritten and typed. One critical skill of written expression is sentence construction: the composition of multiple words that follow rules of semantics and syntax. Unfortunately, many students with disabilities struggle to successfully handwrite or type complete sentences. In the present study, we investigated effects of a supplemental writing intervention that taught simple sentence handwriting and typing. Participants included three elementary students with high-incidence, academically related disabilities. Overall results were mixed with all students showing a gradual increase in sentence typing accuracy and speed as measured by writing sequences on 3-min sentence construction probes. Findings are discussed within the context of multimodal writing development and fluency-based writing interventions.